Street Vendors Based on Tribal Groups in Kendari City, Indonesia - Ashmarita (CV. Literasi Indonesia, 2020)
The main impact of urbanization is to increase urban population density. Increased investment in the industrial sector has opened up job opportunities in various sectors, including the informal sector. Street vendors (PKLs) are one of the informal sector jobs that are often found in plural urban communities. The plurality of the population in society creates different perceptions in terms of the type of work they are engaged in. This study aims to (1). Identify the socio-economic characteristics of PKLs; (2). Identify the strategies used by street vendors in maintaining their existence. This research is a descriptive-qualitative study obtained from interviews and direct observations of PKLs in Kendari. The informants were determined purposively. The analysis data is performed by compiling the data then interpreted by referring to the relationship between various concepts and social realities. The results showed that the street vendors in Kendari were generally villagers. They moved to Kendari because the village where they lived was considered no longer representative of their survival. PKLs are generally urban mobility actors who live on the edge of Kendari. To maintain their existence, they perform various ways, including by strengthening ties between ethnic groups, improving services, finding strategic locations, and making cheaper 'counter' products.